Self selection does not increase other-regarding preferences among adult laboratory subjects, but student subjects may be more self-regarding than adults - Jon Anderson; Stephen V. Burks; Jeffrey Carpenter; Lorenz Götte; Karsten Maurer; Daniele Nosenzo; Ruth Potter; Kim Rocha; Aldo Rustichini (The University of Nottingham, Centre for Decision Research and Experimental Economics (CeDEx), 2010)
We measure the other-regarding behavior in samples from three related populations in the upper Midwest of the United States: college students, non-student adults from the community surrounding the college, and adult trainee truckers in a residential training program. The first two groups were recruited according to procedures commonly used in experimental economics and therefore subjects self-selected into the experiment. Because the structure of their training program reduced the opportunity cost of participating dramatically, 91% of the solicited trainees participated in the third group, so there was little scope for self-selection in this sample. We find no differences in the elicited other-regarding preferences between the self-selected adults and the adult trainees, suggesting that selection into this type of experiment is unlikely to bias inferences with respect to non-student adult subjects. At the same time, we find a large difference between self-selected students and self-selected adults: the students appear considerably less pro-social.
Keywords: C90; D03; 330; methodology; selection bias; laboratory experiment; field experiment; otherregarding behavior; social preferences; truckload; trucker